Risk disclosure and financial performance of Islamic banks in Jordan: the moderating role of financial technology - Almomani, Mohammed Abd-Akarim; Al-Momani, Adai (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Risk disclosure (RD) is important to inform investors. However, few studies examined this variable in developing countries and in Islamic bank context. This research investigates how RD affect financial performance (FP) of Islamic banks in Jordan. It also examines the moderating role of financial technology (FinTech). We use a quantitative method to examine how mandatory risk disclosure (MRD) and voluntary risk disclosure (VRD) impact return on assets (ROA) and return on equity (ROE) in Islamic banks operating in Jordan. Our results show that both MRD and VRD have a significant effect on FP of Islamic banks. Moreover, FinTech acts as a moderator in the connection between risk disclosure (MRD and VRD) and FP performance. The effect was compared before and after coronaviruses disease 2019 (COVID-19) and it shows that the COVID-19 has increased the effect of MRD and VRD on FP of Islamic banks. More focus on VRD and MRD will enhance the FP of Islamic banks in Jordan.